Attenuation of Virulent Porcine Reproductive and Respiratory Syndrome Virus Strain CH-1a and Genetic Variation of ORF5 Gene - Xue-hui CAI; Guo-jun WU; Yong-gang LIU; Guang-qing LIU; Wen-da SHI; Shu-jie WANG; Ping MA; Cheng-jun LI; Wen-yu HAN (Journal of Integrative Agriculture)
To develop a modified live vaccine (MLV) against porcine reproductive and respiratory syndrome virus (PRRSV), virulent CH-1a strain was attenuated by serial passages up to 130 passage (P130) in Marc-145 cells. The virulence and immune efficacy of the attenuated CH-1a were evaluated in pigs. The results showed that animals inoculated with P130 did not develop any clinical sign of the disease, but produced rapid and effective humoral immune responses against PRRSV challenge, indicating that attenuated CH-1a P130 is the candidate as the effective vaccine against PRRSV. To define the potential mutations in the attenuated CH-1a genome, we sequenced and analyzed the ORF5 gene of CH-1a strain of different passages (P39, P55, P65, P70, P85, P100, P115, P120, P125, and P130) and found that three mutations (C5Y, H38Q and L146Q) which may be related with the attenuation of CH-1a. In addition, we also found a unique restriction enzyme site (TspEI) in the ORF5 gene of attenuated CH-1a, which can be used as a genetic marker to distinguish original and attenuated CH-1a.